4-(3-Nitrophenyl)thiazol-2-ylhydrazone derivatives as antioxidants and selective hMAO-B inhibitors: synthesis, biological activity and computational analysis. (1st January 2019) - Secci, Daniela; Carradori, Simone; Petzer, Anél; Guglielmi, Paolo; D'Ascenzio, Melissa; Chimenti, Paola; Bagetta, Donatella; Alcaro, Stefano; Zengin, Gokhan; Petzer, Jacobus P.; Ortuso, Francesco
Abstract: A new series of 4-(3-nitrophenyl)thiazol-2-ylhydrazone derivatives were designed, synthesised, and evaluated to assess their inhibitory effect on the human monoamine oxidase (hMAO) A and B isoforms. Different (un)substituted (hetero)aromatic substituents were linked to N 1 of the hydrazone in order to establish robust structure–activity relationships. The results of the biological testing demonstrated that the presence of the hydrazothiazole nucleus bearing at C4 a phenyl ring functionalised at the meta position with a nitro group represents an important pharmacophoric feature to obtain selective and reversible human MAO-B inhibition for the treatment of neurodegenerative disorders. In addition, the most potent and selective MAO-B inhibitors were evaluated in silico as potential cholinesterase (AChE/BuChE) inhibitors and in vitro for antioxidant activities. The results obtained from molecular modelling studies provided insight into the multiple interactions and structural requirements for the reported MAO inhibitory properties.